Population Density and Habitat Shingle Urchin Preferences (Colobocentrotus atratus) On The Rieting Beach Leupung District Of Aceh - Luthfi Azmi; M Ali Sarong; Samsul Kamal (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
The Information about the presence and density data of Shingle urchin Colobocentrotus atratus in Rieting Beach, Leupung is minimal, so it is necessary to conduct research that aims to determine the population density and habitat preferences of Shingle urchin C. atratus in Rieting Beach, Leupung, Aceh Besar. This study use a quantitative approach (measure with instruments and calculating using the formula) with descriptive research. The data of Population density obtained by survey methods, with using purposive sampling technique. The results were obtained C. atratus population density in Rieting Beach Leupung, Aceh Besar amounted to 2 ind/m2. while the population density in each of the station is the first station to has the density of population is 1 ind/m2. The second station has population density of 3 ind/m2Habitat conditions attached to the substrate C. atratus rocks with the state of heavy waves at a depth of less than 1 meter with a temperature range 26-29°C, 28-32‰ salinity, water pH 6.5-7.6. The conclusions of this study population densities C. atratus in Rieting Beach, Leupung, Aceh Besar, are 2 ind/m2. C. atratus habitat preferences atratus in Rieting Beach is the topography of rock cliffs with 1.5 meters in height with a temperature of 28°C, salinity values 30‰ and pH value 7.Keywords: Density population, Habitat preferences, Colobocentrotus atratus